Bridging the Digital Frontier: The Integration of Social Media Strategy and Promotion in India's Top 10 Institutes of Technology - Arumugam Pitchai; Kuna Sriram; R Rega (International Journal of Information Science and Management)
The rise of globalization has elevated standards for higher education and intensified competition among universities. As a result, higher education institutions increasingly turn to online visibility to gain a competitive advantage. This study examines the social media engagement strategies of India's top 10 Indian Institutes of Technology (IITs), chosen based on their prestigious rankings in the National Institutional Ranking Framework (NIRF). Utilizing a quantitative analysis approach, the research employs social media analytics tools like SocialBlade and Phylanx, alongside manual data collection, to analyze data from platforms such as YouTube, Facebook, LinkedIn, Instagram, and Twitter (now X). The study thoroughly examines metrics including subscribers, likes, posts, views, followers, and engagement rates, revealing the profound impact of social media on higher education institutions. The findings indicate that YouTube, followed by Instagram, leads in user engagement rates among these platforms. Conversely, Facebook, despite having the highest number of followers, shows a relatively lower engagement rate. This detailed analysis offers critical insights into the digital landscape of higher education, emphasizing the role of professional data collection and analysis in crafting effective social media strategies. Such strategies are crucial for enhancing the brand value of educational institutions and navigating the competitive online environment.